MUET webinar 2022: session 1 / Nazima Versay Kudus, Noor Azli Affendy Lee and Isma Noornisa Ismail - Versay Kudus, Nazima; Affendy Lee, Noor Azli; Ismail, Isma Noornisa (Academy of Language Studies, 2022)
A Malaysian University English Test (MUET) webinar was conducted by the MUET Unit, Academy of Language Studies (ALS), UiTM Cawangan Pulau Pinang on 4 February 2022 from 10.00 am - 12.00 pm. The session commenced with the ALS’ Head of Department, Dr Hajah Rofiza Aboo Bakar saying a few words. Then Madam Savina Saiman, a MUET teacher, conducted the session with the attendance of approximately 50 students. Madam Vina, as she is fondly known, began her session by explaining the revision made in the new MUET where each test component now receives similar weightage which demonstrates that all four language skills are equally important. Another revision is that the aggregated score will be in accordance with the CEFR global scale; instead of having six bands, the latest one only has five.